Antioxidant activity and solubility of green mussel (Perna Viridis) hydrolysate as influenced by degree of hydrolysis / Normah Ismail and Fadilah Mohd Hasni - Mohd Hasni, Fadilah (UiTM Perlis, 2014)
Antioxidant activity and solubility of green mussel (Perna viridis) hydrolysate prepared by hydrolysis with Alcalase 2.4L under two different conditions (pH7, enzyme substrate ratio (ES) 5% and pH 9, ES 3%) were investigated. Green mussel hydrolysate exhibited free radical scavenging effect where pH7, ES 5% hydrolysate had higher radical scavenging effect than pH9, ES 3% hydrolysate. The degree of hydrolysis (DH) achieved were 43.81% and 28.33% for hydrolysis at pH9, ES 3% and pH7, ES 5%, respectively. Results revealed that antioxidant activity and solubility of green mussel hydrolysate were influenced by DH where the antioxidant activity was higher at low DH and the hydrolysate was more soluble at high DH. Antioxidant activity was more stable when the hydrolysate was stored at 4°C compared to 25°C but gradually decreased during the seven day storage period at both temperatures. Based on the solubility and antioxidant properties, green mussel hydrolysate has the potential to be used in several food applications as natural food additive.